KARAKTERISTIK FISIK DAN DAYA TERIMA KUE BARUASA DENGAN SUBTITUSI TEPUNG MOCAF - Nur fahmi; Hendrayati Hendrayati; zakaria Zakaria; Thresia Dewi Kartini (Jurusan Gizi Poltekkes Kemenkes Makassar, 2017)
Background : MOCAF is a cassava flour product processed using the principle of modifying cassava cells by fermentation. The growing microbes cause characteristic changes of the resulting starch in the form of increased viscosity, gelability, rehydration, and ease of solubility.Objective : This study aims to determine the physical characteristics and acceptance of Kue Baruasa with substitution of MOCAF flour for PMT pregnant mothers in District Moncongloe Maros Regency.Method : This research is a quasi-experimental research. The sample is Kue Baruasa substitution of MOCAF flour with concentration of 100%, 75%, 50% and 0%. The panel of received power consists of 35 students and 10 pregnant women. The research was conducted in food laboratory of Poltekkes Kemenkes Makassar Nutrition Department, Laboratory of State Polytechnic of Ujungpandang and District of Moncongloe of Maros Regency. Result : The results showed that the lowest level of hardness was found in Kue Baruasa with concentration of 75%. There were no color differences in the four groups of samples (p = 0.434). There were differences of taste in the four groups of samples (p = 0.010). There were differences of aroma in the four groups of samples (p = 0.010). There was a difference of texture in all four groups of samples (p = 0,009). The nutritional content of the Mosaic Cookies is lower than the nutrient content of pregnant PMT biscuits distributed by the Ministry of Health.Conclusion : It is suggested that Barca Substitute Cake substitution of MOCAF 50% gets better reception by panelist and the nutrient content of Kue Baruasa still needs to be improved in order to reach the standard of PMT for pregnant mother.Keywords : Mocaf, PMT, Pregnant mothers